VD_FINDINFO Jug / 2019 / 209 vom 12. Januar 2018 - VD Tribunal cantonal (2018)
DÉPENS, MAXIME INQUISITOIRE, OBLIGATION DE CHIFFRER LES CONCLUSIONS | 107 al. 2 LTF, 429 al. 1 let. a CPP (CH), 429 al. 2 CPP (CH), 432 al. 2 CPP (CH)